REKONTEKSTUALISASI PENDIDIKAN AGAMA ISLAM DALAM BINGKAI TEOLOGI INKLUSIF - Muhamad Januaripin; Ubed Jubaedah; Munasir (KAMALIYAH : Jurnal Pendidikan Agama Islam, 2025)
The plural social reality of Indonesia demands that Islamic Religious Education (PAI) develop religious competencies that are more dialogical, tolerant, and adaptive to diversity. However, various studies indicate that PAI is still dominated by a normative-doctrinal paradigm and therefore has not been able to adequately respond to the dynamics of pluralism. This article critically analyzes how inclusive theology can be recontextualized within PAI as an alternative approach to addressing the challenges of religious pluralism. This study employs a literature review method by examining recent scholarly works to identify developments in theories of pluralism, inclusive theology, and PAI learning. The findings reveal that inclusive theology offers a theological foundation for strengthening religious moderation, interreligious literacy, and dialogical pedagogy as a new framework for PAI. Thus, recontextualizing PAI through an inclusive theological perspective becomes urgent through curriculum reformulation, pedagogical revitalization, and the strengthening of teacher competencies. These findings contribute to the development of a more humanistic PAI paradigm capable of nurturing diversity within Indonesia’s multicultural context.